All Days 1998
DOI: 10.2118/51086-ms
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Bubblepoint Pressures for Reservoir Oils--A Comparative Study

Abstract: None of the currently proposed correlations for bubblepoint pressure am particularly accurate.Knowledge of bubblepoint pressure is one of the important factors in the primary and subsequent developments of an oil field. Bubblepoint pressure is required for material balance calculations, analysis of well performance, reservoir simulation, and production engineering calculations.In addition, bubblepoint pressure is an ingredient, either directly or indirectly, in every oil properly correlation. Thus an error in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 10 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…This error is found to be within the error bound of 13% suggested by McCain et al 35 . The common thing between the present model and that of Al-Marhoun (1988) 10 correlation, is that they both were developed for Saudi Crude oils; this supports the idea of developing local/regional correlations for predicting PVT properties rather than universal ones which recommended by other researchers 23 .…”
Section: Bubble-point Pressure (Pb) Modelsupporting
confidence: 84%
See 1 more Smart Citation
“…This error is found to be within the error bound of 13% suggested by McCain et al 35 . The common thing between the present model and that of Al-Marhoun (1988) 10 correlation, is that they both were developed for Saudi Crude oils; this supports the idea of developing local/regional correlations for predicting PVT properties rather than universal ones which recommended by other researchers 23 .…”
Section: Bubble-point Pressure (Pb) Modelsupporting
confidence: 84%
“…In their comparative study, McCain et al 35 considered three independent means for developing P b correlations, namely, non-linear regression of a model, neural network models, and non-parametric regression. Using 728 global data sets; they found that the best possible correlations of P b are accurate to an average absolute error of about 13 percent.…”
Section: Pvt Neural Network Modelsmentioning
confidence: 99%
“…However, the method that was used here is based on the Alternating Conditional Expectation (ACE) algorithm [26,27]. A comparison between Neural Network and ACE algorithm was used to build bubble point pressure correlation for oil reservoirs [28] and it was found that the predictive strength of ACE is much higher compared to Neural Network for the studied samples. The ACE algorithm is based on the concept of developing non-parametric transformations of the dependent and independent variables.…”
Section: Non-parametric Regression Analysismentioning
confidence: 99%
“…However, parametric regressions may yield erroneous and even misleading results when the relationship between the dependent and the independent variables is unknown (Jensen and Lake, 1985;Wendt et al, 1986;Xue et al, 1997). More recently, nonparametric methods based on successive refinements have gained wide popularity in a variety of disciplines ranging from engineering to air and soil pollution control (Steele, 1990;Gordon et al, 1993;Smith, 1994;McCain et al, 1998;Al-Ajmi and Holditch, 2001;Nashawi and Malallah, 2006;2009). The main advantage of these techniques is that they define the regression surface in an iterative fashion while remaining completely data driven as opposed to other model driven correlations.…”
Section: Nonparametric Optimal Transformationsmentioning
confidence: 99%